Effect of type of coagulants on removal efficiency and removal mechanisms of antibiotic resistance genes in anaerobic digestion of primary sludge produced via a chemically enhanced primary treatment process. (February 2022) - Mezemir Damtie, Mekdimu; Shin, Jingyeong; Lee, Sungman; Min Park, Chang; Wang, Jinhua; Mo Kim, Young
Graphical abstract: Highlights: Impact of coagulants (Fe 3+ and Al 3+ ) on ARGs removal was investigated during AD. AD of primary sludge with FeCl3 achieved up to 72.1% removal in total of 23 ARGs. AD with PACl rapidly removed ARGs during the initial operational period. Coagulants had no impact on changes in microbial community during AD. tet BP had a significantly positive correlation only with the Cloacimonetes phylum. Abstract: The potential impact of the trivalent coagulant cations on the removal mechanisms, removal efficiencies and removal patterns of antibiotic resistance genes (ARGs) during anaerobic digestion (AD) of chemically enhanced primary treatment sludge (CEPTS) was investigated using polyaluminium chloride (PACl), ferric chloride (FeCl3 ) and mixed FeCl3 -PACl. The removal efficiency of 23 ARGs and intI 1 improved to 72.1% in AD of primary sludge with 100 mg/L FeCl3 and was lowest (only 54.4 %) in AD of primary sludge with 25 mg/L PACl. The removal of ARGs in AD of CEPTS with addition of single or mixed types of Al-based coagulant began to increase rapidly at the onset of batch operation. On the other hand, both the rapid increase in the removal efficiency of ARGs in AD with FeCl3 and the maximum removal efficiency were attained later than in the other ADs.